Heterogeneous Sodium‐Manganese Oxide Catalyzed Aerobic Oxidative Cleavage of 1, 2‐Diols. Issue 32 (5th July 2017) - Escande, Vincent; Lam, Chun Ho; Coish, Philip; Anastas, Paul T.
Abstract: The aerobic oxidative cleavage of 1, 2‐diols using a heterogeneous catalyst only based on earth‐abundant metals manganese and sodium is reported for the first time. This reusable catalyst cleaves a variety of substrates into aldehydes or ketones with high selectivity. The reaction requires small catalytic loadings and is performed under mild conditions using ambient pressure O2 or air as the oxidant while producing water as the only by‐product. Mechanistic investigations reveal a monodentate, two‐electron oxidative fragmentation process involving a Mn IV species. The eco‐friendly, innocuous catalyst is compatible with a wide range of functional groups and conditions, making it highly competitive with classical reagents, such as periodic acid or lead tetraacetate, as a preferred method for activated 1, 2‐diols. Abstract : Catalytic scissors : A reusable heterogeneous catalyst, easily prepared from earth‐abundant elements Na and Mn, cleaved 1, 2‐diols by using atmospheric O2 as the sole oxidant and forming water as the only by‐product. Aldehydes or ketones are formed with high yield and selectivity, making this eco‐friendly method a competitive alternative to classical reagents.